Uma investigação sobre os instrumentos avaliativos de um curso de LE utilizando planejamento temático baseado em tarefas para professores pré-serviço de contexto adverso - Batocchio, Luciana Renata (2013)
In this research we realize an investigation into the assessment process in a course of English Language using a thematic task-based planning for teachers pre-service of adverse context of a private college in the state of São Paulo, and check if there or not the compatibility of the assessment instruments and activities of teaching material - "A Short Historical Sketch of Britain" (Barbirato, 2005) with such planning principles, criteria and tasks definitions. Being aware that the evaluation process should understand the context researched in evaluative instruments that are consistent with the instruction given in the classroom, we list the purpose of this study to ascertain the extent to which these instruments measure facilitated the learning of FL through a theme, seeking the meaning of language and communication as the main unease in this area is to find a way to evaluate the student consistent with such instruction. We choose a qualitative interpretative in nature, through the gathering of evaluative data documents used throughout the course, as well as a questionnaire for teacher s course who contributed to the triangulation of the data analyzed. The results allowed us to infer that the evaluative instruments, although some still aren t the most appropriate measure progress achieved before the student's ability to communicate at English Language. However, analysis of the data documents revealed that although some instruments, especially the written evaluations, require changes to be in line with course design model implemented one the planning in question, can say that it contributed to reaching a positive evaluation in this context.